(untitled) (Maritime Park: Journal of Maritime Technology and Society, 2024)
Oil & gas drilling in the open sea cannot be avoided with the use of FPSO. Floating Production Storage and Offloading (FPSO) is a facility in the form of a floating production storage and unloading vessel in the form of crude oil and natural gas originating from the seabed. The selected type of floater that will be operated in the Abadi field, Masela Block, Arafura Sea is the Azurite FPSO ship. In its operation, the FPSO will not be separated from the influence of dynamic loads such as sea waves, ocean currents and wind on the mooring rope structure periodically. This may cause damage to the structure mooring line which influences the performance of the structure. The aim of this research is to analyze motion trajectory (surge and sway), mooring line stress, and fatigue damage on the mooring system catenary by making comparisons using variations in mooring depth. Dimensions mooring line type chain on fairlead with six (6) variations in mooring depth, namely 1000, 900, 800, 700, 600 and 500 meters which will then be analyzed fatigue damage from mooring line the. Observation result Motion Trajectory It was found that the shallower the mooring depth mooring line then value ∆Offset or movement surge & sway will get bigger. Meanwhile in observations Mooring Line Stress and Fatigue Damage obtained both are directly proportional where the greater the tension mooring line then the ratio of damage that occurs due to fatigue in the structure will also be greater. This is because the mass of the rope used is not proportional to displacement boat. And in this numerical analysis simulation it only reaches the initial movement, namely at 100 seconds, where the ship’s condition has not yet reached the stable condition it should be.